Anti-Allergic Inflammatory Activity of Interleukin-37 Is Mediated by Novel Signaling Cascades in Human Eosinophils - Zhu, Jing; Dong, Jie; Ji, Lu; Jiang, Peiyong; Leung, Ting Fan; Liu, Dehua; Ng, Lai Guan; Tsang, Miranda Sin-Man; Jiao, Delong; Lam, Christopher Wai-Kei; Wong, Chun-Kwok (Frontiers in Immunology, 2018)
IL-1 family regulatory cytokine IL-37b can suppress innate immunity and inflammatory activity in inflammatory diseases. In the present study, IL-37b showed remarkable in vitro suppression of inflammatory TNF-α, IL-1β, IL-6, CCL2 and CXCL8 production in the co-culture of human primary eosinophils and human bronchial epithelial BEAS-2B cells with the stimulation of bacterial toll-like receptor-2 (TLR2) ligand peptidoglycan (PGN), while antagonizing the activation of intracellular nuclear factor-κB, PI3K-Akt, extracellular signal–regulated kinase (ERK)1/2 and suppressing the gene transcription of allergic inflammation-related PYCARD, S100A9 and CAMP as demonstrated by flow cytometry, RNA-sequencing and bioinformatics. Results therefore elucidated the novel anti-inflammation-related molecular mechanisms mediated by IL-37b. Using the house dust mite-induced humanized asthmatic NOD/SCID mice for pre-clinical study, intravenous administration of IL-37b restored the normal plasma levels of eosinophil activators CCL11 and IL-5, suppressed the elevated concentrations of Th2 and asthma-related cytokines IL-4, IL-6 and IL-13 and inflammatory IL-17, CCL5 and CCL11 in lung homogenate of asthmatic mice. Histopathological results of lung tissue illustrated that IL-37b could mitigate the enhanced mucus, eosinophil infiltration, thickened airway wall and goblet cells. Together with similar findings using the ovalbumin- and house dust mite-induced allergic asthmatic mice further validated the therapeutic potential of IL-37b in allergic asthma. The above results illustrate the novel IL-37-mediated regulation of intracellular inflammation mechanism linking bacterial infection and the activation of human eosinophils, and confirm the in vivo anti-inflammatory activity of IL-37b on human allergic asthma.